Early Enteral Nutrition and Short-Term Laboratory Dynamics in Acute Stroke With Dysphagia: Hemorheology, Inflammatory Cytokines, and Intestinal Barrier Biomarkers: Enteral Nutrition, Stroke & Dysphagia: Microcirculation and Cytokines - Wang, Yanping; Wang, Yuan (Journal of Medical Biochemistry, 2026)
Background:To examine whether enteral nutrition support modulates blood microcirculation, stress-related cytokines, and nutrition/metabolism biochemical indices in patients with acute cerebral stroke (CS) complicated by swallowing disorders (SD), and to explore possible biochemical links among these changes. Methods:This retrospective cohort study included 126 patients with acute CS complicated by SD admitted to our hospital from August 2022 to August 2025. According to the intervention plan, patients were assigned to an observation group (68 cases; enteral nutrition support) or a control group (58 cases; routine fluid replacement therapy). Fasting venous blood was collected before intervention (T0), at 7 days (T1), and at 14 days (T2). Hemorheological parameters and red blood cell functional indices were measured with an automatic hemorheology analyzer; stress cytokines, inflammatory mediators, and intestinal barrier–related indicators were quantified by enzyme-linked immunosorbent assay; nutrition metabolism–related indices were determined using an automatic biochemical analyzer. Results:In the observation group, hemorheological parameters improved progressively after intervention. Compared with T0, whole-blood high-shear viscosity (W-Vis-H), whole-blood low-shear viscosity (W-Vis-L), and fibrinogen were lower at T1 and further reduced at T2, while the red blood cell deformation index (RDI) increased (P<0.05). Stress cytokines, inflammatory mediators, and intestinal barrier indicators declined in parallel. By T2, tumor necrosis factor-α, interleukin-6, high-sensitivity C-reactive protein, and endotoxin each decreased by more than 35% versus T0 (P<0.05). Nutrition metabolism indices increased gradually: prealbumin (PA) and transferrin (TRF) increased at T1, and six indicators (including albumin [ALB] and hemoglobin [Hb]) showed statistically significant improvements at T2 (P<0.05). No significant changes were observed in these indices at any time point in the control group (P>0.05). Between-group comparisons showed more favorable values in the observation group at T1 and T2 (P<0.05). Conclusion:In patients with acute CS complicated by SD, enteral nutrition support was associated with short-term stabilization of biochemical homeostasis, including improved microcirculation-related hemorheology, suppression of excessive inflammatory/stress responses, and reinforcement of nutritional reserves.